Pengaruh Nilai Output Dan Jumlah Unit Usaha terhadap Penyerapan Tenaga Kerja Pada Industri Besar dan Sedang di Provinsi Sumatera Utara - Berkat Juni Krisman Gulo; Iman Totonafo Saro Hia; Widya Kartika; Ahmad Albar Tanjung (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to provide an explanation of the effect of output value and number of business units on employment in large and medium industries in 8 cities in North Sumatra Province. This research is a quantitative research with descriptive method with data collection techniques in documentation. The use of data in this study uses cross section and time series data taken from 8 cities in North Sumatra Province in 2010-2019. Regression analysis used in this study is panel data regression analysis with E-Views 10 analysis tool. The results of the study show that partially (t test) the output value and the number of business units have a positive and significant effect on employment in large and large industries. currently. Simultaneously (f test) the output value and the number of business units have a significant effect on employment in large and medium industries.